2010
DOI: 10.1002/jcu.20743
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings in Nicolau syndrome following intramuscular diclofenac injection: A case report

Abstract: Nicolau syndrome (also known as embolia cutis medicamentosa and livedoid dermatitis) is a rare but severe localized adverse drug reaction of intramuscular injection of various drugs. The typical presentation is pain around the injection site soon after injection, followed by erythema, livedoid patch, hemorrhagic patch, and finally necrosis of skin, subcutaneous fat, and muscle tissue. We report a case that occurred in a 34-year-old woman after intramuscular injection of diclofenac sodium. Sonography showed dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
1
15
0
3
Order By: Relevance
“…Diclofenac is a well‐known NSAID and often used to relief skeletal muscle pain, but extremely few adverse effects on mature skeletal muscle have been reported thus far. Recently, a case report described that a 34‐year‐old woman after intramuscular injection of diclofenac sodium suffered an extensive edema on gluteal and piriformis muscles (Park et al, 2011). Therefore, diclofenac has adverse effect on adult's muscles although the reported case is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac is a well‐known NSAID and often used to relief skeletal muscle pain, but extremely few adverse effects on mature skeletal muscle have been reported thus far. Recently, a case report described that a 34‐year‐old woman after intramuscular injection of diclofenac sodium suffered an extensive edema on gluteal and piriformis muscles (Park et al, 2011). Therefore, diclofenac has adverse effect on adult's muscles although the reported case is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Marangi et al showed this macroscopically by dissecting the necrotic area on a thrombotic vessel [16]. This viewpoint was also supported by sonographic findings of Park et al and mirror Doppler mapping of nonaffected cutaneous territories by Uri and Arad in NS cases [7,17]. Focal thrombosis in associated vessels was also observed in [4].…”
Section: Discussionmentioning
confidence: 75%
“…En nuestro caso, el diagnóstico fue clínico, la sonografía evidenció edema de partes blandas en región glútea y la biopsia de piel reportó necrosis marcada de células de la epidermis, trombosis en plexos vasculares medios y profundos. 1,15 En la mayoría de los casos el pronóstico del síndrome de Nicolau es la curación, con cicatrices atróficas o pigmentación restantes, como ocurrió en nuestro paciente. No obstante, en casos raros, puede causar complicaciones como hipoestesia, paraplejia, deficiencia del esfínter o sepsis.…”
Section: Discussionunclassified